Proprioceptive art: How should it be defined, and why has it become so popular?. (September 2022) - Spence, Charles
In recent years, there has been something of an explosion of interest in those artworks and installations that directly foreground the bodily senses. Often referred to as proprioceptive (or prop.) art, the question to be addressed in this narrative historical review is how it should be defined, and why has it become so popular? A contrast is drawn with examples of sculpture and/or tactile art. The entertainment/experiential element of such works cannot be denied, especially in an era where funding in the arts sector is so often linked to footfall. At the same time, however, a number of the works appear to be about little more than entertainment/amusement. One might wonder why such "edutainment" should be placed in the art gallery rather than, say, in a museum of science or illusion. Nevertheless, in the best cases, the foregrounding, or removal, of bodily sensations that proprioceptive artworks deliver can potentially help to connect people in an increasingly digital, online, mostly audiovisual, and hence in some sense disembodied contemporary existence. These issues are discussed in the context of the works of Carsten Höller, a prolific German installation and object artist.